Ovarian Tissue Transplantation: Experience From Germany and Worldwide Efficacy - Laura Lotz; Ralf Dittrich; Inge Hoffmann; Matthias W Beckmann (SAGE Publishing, 2019)
Extraction of ovarian tissue prior to oncologic therapy and subsequent transplantation is being performed increasingly often to preserve fertility in women. The procedure can be performed at any time of the cycle and, therefore, generally does not lead to any delay in oncological therapy. Success rates with transplantation of cryopreserved ovarian tissue have reached promising levels. More than 130 live births have been reported worldwide with the aid of cryopreserved ovarian tissue and the estimated birth rate is currently approximately 30%. In Germany, Austria, and Switzerland, the FertiPROTEKT consortium has successfully achieved 21 pregnancies and 17 deliveries generated after 95 ovarian tissue transplantations by 2015, one of the largest case series worldwide confirming that ovarian tissue cryopreservation and transplantation are successful. Approximately, more than 400 ovarian tissue cryopreservation procedures are performed each year in the FertiPROTEKT consortium, and the request and operations for ovarian tissue transplantation have increased in recent years. Therefore, recommendations for managing transplantation of ovarian tissue to German-speaking reproductive medicine centers were developed. In this overview, these recommendations and our experience in ovarian tissue transplantation are presented and discussed with international procedures.